On the Size and Professional Composition of RAS Academicians and Corresponding Members - A. S. Kulagin (Ekonomika Nauki)
This opinion piece critically examines the transformation of the Russian Academy of Sciences (RAS) following its 2013 reform, highlighting systemic issues in its membership composition. The author argues that the 71% postreform surge in academicians (to 941 by 2025) has eroded the prestige of RAS titles, exacerbated by the election of non-scientists (officials, politicians, business figures) and instances of nepotism. Drawing on historical precedents from the USSR era, the paper advocates for legislative reforms to restore academic integrity. Key proposals include legally defining «scientist» to exclude non-professionals, reinstating USSR-style justification protocols for new academic seats, restricting financial benefits to active researchers, and leveraging the newly established RAS Trusteeship Council to enforce criteria. The article underscores the urgency of these measures to prevent further devaluation of RAS authority and ensure Russia’s scientific development.